Potencial anti-inflamatório e antiproliferativo de compostos inibidores da enzima desoxi-hipusina sintase - Almeida Junior, Oedem Paulo de [UNESP] (2015)
eIF5A is the only known protein containing the unusual amino acid residue hypusine (hydroxiputrescine-lysine). This hypusine residue is essential for eIF5A function and it is formed by modifying a specific lysine residue in a posttranslational reaction dependent on the polyamine spermidine. The modification of the lysine residue for the formation of hypusine is called hypusination, which occurs in two steps: first, the enzyme deoxyhypusine-synthase (DHPS) transfers the 4-aminobutyl moiety from spermidine to a specific lysine residue in eIF5A (position 50 in mammals); then it is hydroxylated by deoxyhypusine-hydroxylase (DOHH). Many authors have demonstrated that inhibition of hypusination by the DHPS inhibitor GC7 or silencing eIF5A leads to inhibition of cell proliferation in several types of mammalian cells, including tumor cell lines, and also induce an anti-inflammatory effect, as evidenced in a murine model of diabetes and sepsis. This study aimed to use the macrophage cell line RAW 264.7 to better understand the mechanisms by which GC7 has its activity. Complementarily, its was also tested the effect of GC7 in primary culture of macrophages and in rats. As expected, we show here that GC7 inhibits hypusination in RAW 264.7 cells and, on the other hand, this treatment with GC7 does not compromise cell viability nor significantly alter the proteome of RAW 264.7 cells. Moreover, GC7 inhibits the production and release of TNF-α without affecting mRNA levels of this cytokine, indicating a posttranscriptional modulation, most probably at the translational level, given the eIF5A function in the process of protein synthesis. Interestingly, this inhibitory effect on TNF-α release was also observed in primary cultures of macrophages and in vivo in rats. It was also examined the GC7 ability to inhibit cell proliferation of RAW 264.7 cells, which occurs prior to the S phase of the cell cycle and does not...